Finite element modelling and experimental validation in radiative heat transfer. - Mile R Vujicic (2006)
The work presented in this thesis can be divided into two parts: numerical modelling and experimental validation. The first part considers a finite element computer code called Pharo which has been developed to simulates heat transfer exchanged in an enclosure via thermal radiation and conduction. This finite element heat transfer code has been written for the Defence, Science and Technology Laboratory (DSTL). Face to face (zonal) thermal radiation which operates with diffuse surface properties of materials without a participating media is analyzed and included in Pharo. To analyze the net heat exchanged within an enclosure several methods for view factor calculation, such as the Monte Carlo and Hemi-cube methods were included in Pharo. During heat transfer simulations a better accuracy of results has been demonstrated using a new approach called the Multiple Reflection of View Factors 'MRV' method. Transient heat flow is solved using both finite difference and finite element time stepping. Also, an analysis of transient heat flow using different solvers (direct and iterative) to find the most appropriate one was carried out. The second part of the work considers experimental validation of numerical results obtained using Pharo. Special attention was given to the analysis of the relationship between view factors and measured heat transfer. To make the experimental data complete the measurements of surface properties including emissivity, reflectivity for different wavelengths as well as roughness of materials is presented. These experimental results can be used as experimental benchmark data for model users and developers.